Solvent Evaporation Method and Crystal Structure of bis-(5-Bromo-2-methyl-phenyl)diazene - He, Y.X. (Asian Journal of Chemistry, 2015)
One new diazene compound from 4-methoxybenzenamine, CuBr and 2,2,6,6-tetramethylpiperidin-1- yl)oxidanyl (TEMPO) has been successfully synthesized. Compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.